2019
DOI: 10.3389/fpsyg.2019.01960
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Controlled Trial of a Play-Based, Peer-Mediated Pragmatic Language Intervention for Children With Autism

Abstract: PurposeThis randomized controlled trial evaluated the effectiveness of a play-based pragmatic language intervention for children with autism.MethodsA sample of 71 children with autism were randomized to an intervention-first group (n = 28 analyzed) or waitlist-first (n = 34 analyzed) group. Children attended 10, weekly clinic play-sessions with a typically developing peer, and parents mediated practice components at home. The Pragmatics Observational Measure (POM-2) and the Social Emotional Evaluation (SEE) ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 50 publications
1
17
1
Order By: Relevance
“…TD-playmates were expected to act as a key agent of change within this intervention, particularly for the facilitation of skills maintenance and generalisation for their peers with autism, as children were likely to continue to play and interact away from the clinic environment. These maintenance and generalisation findings for TD-playmates mirror those of their peers with autism (Parsons et al, 2019b), suggesting that TD-playmates may have assisted in facilitating the desired skills maintenance and generalisation for their peers with autism. However, the interaction between gains, maintenance and generalisation made by children within each dyad…”
Section: Discussionmentioning
confidence: 77%
See 4 more Smart Citations
“…TD-playmates were expected to act as a key agent of change within this intervention, particularly for the facilitation of skills maintenance and generalisation for their peers with autism, as children were likely to continue to play and interact away from the clinic environment. These maintenance and generalisation findings for TD-playmates mirror those of their peers with autism (Parsons et al, 2019b), suggesting that TD-playmates may have assisted in facilitating the desired skills maintenance and generalisation for their peers with autism. However, the interaction between gains, maintenance and generalisation made by children within each dyad…”
Section: Discussionmentioning
confidence: 77%
“…This study aimed to investigate the pragmatic language outcomes for TD-playmates involved in a peer-mediated, play-based pragmatic language intervention for children with autism. Results indicated that the pragmatic language performance (POM-2) of the typicallydeveloping peers improved significantly over the 10-weeks of intervention, effects were maintained 3-months later, and scores were equivalent across the clinic and home environments; mirroring the results of their peers with autism (Parsons et al, 2019b). It was expected that TD-playmates would refine and impart the pragmatic language skills required to maintain a positive social-play interaction, as peer-modelling is a driver of change for target children in peer-mediated interventions.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations